2008
DOI: 10.1101/gad.1650608
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific regulation of SIRT1 by calorie restriction

Abstract: Calorie restriction (CR) has been reported to increase SIRT1 protein levels in mice, rats, and humans, and elevated activity of SIRT1 orthologs extends life span in yeast, worms, and flies. In this study, we challenge the paradigm that CR induces SIRT1 activity in all tissues by showing that activity of this sirtuin in the liver is, in fact, reduced by CR and activated by a high-caloric diet. We demonstrate this change both by assaying levels of SIRT1 and its small molecule regulators, NAD and NADH, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
431
6
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 522 publications
(461 citation statements)
references
References 28 publications
23
431
6
1
Order By: Relevance
“…Table 1 summaries some of the most important signaling molecules involved in CR-induced biological and physiological responses. FOXO ↓ [89,97] GSK-3β ↓ [93,98] HIF-1 ↓ [95,99] HSF-1 ↑ [94] HSP-70 ↑ [94,100] mTOR ↓ [90,101] NF-κB ↓ [81,82,95,97] PGC-1α ↑ [91,92] PPAR α ↑ [91,102] SIRT1 ↑↓ [92,93,103] ↑=increase in signal transduction; ↓=decrease in signal transduction.…”
Section: Signal Transduction Mechanism Involved In Crmentioning
confidence: 99%
“…Table 1 summaries some of the most important signaling molecules involved in CR-induced biological and physiological responses. FOXO ↓ [89,97] GSK-3β ↓ [93,98] HIF-1 ↓ [95,99] HSF-1 ↑ [94] HSP-70 ↑ [94,100] mTOR ↓ [90,101] NF-κB ↓ [81,82,95,97] PGC-1α ↑ [91,92] PPAR α ↑ [91,102] SIRT1 ↑↓ [92,93,103] ↑=increase in signal transduction; ↓=decrease in signal transduction.…”
Section: Signal Transduction Mechanism Involved In Crmentioning
confidence: 99%
“…The results also raise the possibility that SIRT1 may not be the only factor, but rather one of several components that regulate CR-mediated lifespan extension, as neither overexpression of SIRT1 nor resveratrol extended lifespan in mammals. Notably, Chen et al (2008) showed that CR does not increase SIRT1 in whole tissue. It is likely that the use of tissue-specific SIRT1 transgenic mice could be more effective in clarifying the role of SIRT1 in CR-mediated lifespan extension.…”
Section: Resultsmentioning
confidence: 99%
“…SIRT1 in the hypothalamic arcuate nucleus SIRT1, the most extensively studied member of the sirtuin family, regulates energy metabolism in the hypothalamus and is induced by a negative energy balance (Chen et al, 2008;Cohen et al, 2004). SIRT1 is expressed in the orexigenic neuropeptide Y (NPY)/Agouti-related peptide (AGRP) and anorexigenic proopiomelanocortin (POMC) neurons, which are major components in regulating feeding and energy expenditure in the arcuate nucleus of the hypothalamus (Sasaki and Kitamura, 2010).…”
Section: Sirt1mentioning
confidence: 99%
See 1 more Smart Citation
“…Steatosis is accompanied by liver inflammation, with an increase in TNF and IL-1 synthesis and in total macrophage markers such as F4.80. However, it must be noted that Guarente's team has observed an opposite outcome in a similar model of liver-specific SIRT1 deletion, with SIRT1 absence proving to have a beneficial effect on several metabolic parameters following HFD, even if no effect on NFkB acetylation or liver inflammation was reported [30]. The increase in F4.80 expression in Purushotham's study suggests an important macrophage infiltration and this prompted the authors to disrupt SIRT1 in macrophages and assess the consequences of HFD feeding [29].…”
Section: Sirt1 Negatively Regulates Nfkb Activitymentioning
confidence: 99%